Efficient waterproof layer structure type cable
By adding extruded crosslinked fluororesin masterbatches to the outer sheath layer of the cable and blended with polyolefin, the problem of insufficient waterproofing effect of existing waterproof cables in humid or underwater environments is solved, achieving more efficient waterproofing performance and longer service life.
Patent Information
- Application Number
- CN202411789878.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-25
AI Technical Summary
Existing waterproof cables are insufficiently waterproof in wet or underwater environments, resulting in a shorter service life of the cable and an increased maintenance frequency in these environments.
A layer-structured cable design is adopted, in which the outer sheath layer is blended and extruded with polyolefin by adding extruded crosslinked fluororesin masterbatches to form an outer sheath layer with high hydrophobicity and waterproof properties.
Significantly improves the waterproof performance of the cable in wet or underwater environments, extends the service life of the cable and reduces the frequency of maintenance and replacement.
Smart Images

Figure CN119517502A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wire and cable product design, and in particular relates to a highly efficient and waterproof layer structure cable. Background Art
[0002] Waterproof cables are widely used in humid or near-water environments. Waterproof cables can effectively prevent moisture penetration and ensure the normal operation of cables in humid or underwater environments, thereby ensuring the stability and safety of electrical systems, extending the service life of cables, and reducing the frequency of maintenance and replacement.
[0003] At present, some waterproof cables are equipped with a special waterproof layer for waterproofing and water isolation, which not only increases the number of layers of the cable, but also increases the production process. Therefore, more and more cables are gradually becoming waterproof mainly through the material design of the cable outer sheath. For example, fluororesin is added to the cable sheath. On the one hand, the CF bond in the fluororesin itself has a very high bond energy, and the fluorine atoms in the resin also have a tendency to migrate to the surface of the protective sheath, which reduces the surface energy of the protective sheath, thereby showing a waterproof performance that is superior to other resins. Summary of the invention
[0004] In order to further improve the waterproof effect of the cable, the present invention provides a highly efficient waterproof layer structure cable, comprising one or more insulating shielded wire cores, each insulating shielded wire core comprises a conductor wire core, an insulating layer tightly wrapped outside the conductor wire core, and a shielding layer tightly wrapped outside the insulating layer; all the insulating shielded wire cores are twisted together and tightly wrapped by a flame retardant layer, and the cable also includes an outer sheath layer tightly wrapped outside the flame retardant layer.
[0005] The outer sheath layer is calculated by weight and includes 100 parts of polyolefin, 10-20 parts of fluororesin masterbatch, 10-20 parts of POE elastomer, 1-2.5 parts of the first lubricant, 0.1-0.5 parts of antioxidant, and 3-10 parts of plasticizer.
[0006] The fluororesin masterbatch comprises, by weight, 100 parts of polyvinylidene fluoride, 0.3-0.6 parts of a cross-linking agent, and 1-2 parts of a second lubricant.
[0007] Preferably, there are more than two insulating shielding cores, and the gaps between the insulating shielding cores inside the flame retardant layer are filled with filling ropes.
[0008] Preferably, each conductor core is formed by twisting a number of round copper wires.
[0009] Preferably, the aluminum-plastic tape is evenly wrapped around the insulation layer as a shielding layer.
[0010] Preferably, the insulated shielded wire cores twisted together are uniformly wrapped with mica tape as a whole, thereby forming a flame retardant layer outside the insulated shielded wire cores.
[0011] Preferably, the polyolefin is polyethylene or polypropylene.
[0012] Preferably, the fluororesin masterbatch is prepared by adding polyvinylidene fluoride, a crosslinking agent and a second lubricant into a high-speed mixer, stirring and mixing them sufficiently, and then adding them into an extruder for blending, extrusion and granulation.
[0013] Preferably, the crosslinking agent is a peroxide crosslinking agent, such as dicumyl peroxide.
[0014] Preferably, the first lubricant and the second lubricant are zinc stearate, calcium stearate, etc.
[0015] Preferably, the antioxidant is a phenolic antioxidant, such as antioxidant 1010.
[0016] As a preferred plasticizer, dioctyl phthalate or the like is used.
[0017] Preferably, the outer sheath layer is prepared by adding polyolefin, fluororesin masterbatch, POE elastomer, first lubricant, antioxidant and plasticizer into a high-speed mixer, stirring and mixing them sufficiently, and then adding them into an extruder for blending, extrusion and granulation to obtain the outer sheath layer masterbatch. The outer sheath layer masterbatch is then melted in the extruder, uniformly extruded on the surface of the flame retardant layer, and cooled to form the outer sheath layer.
[0018] The method for preparing a highly efficient waterproof layer structure cable is:
[0019] After the insulating layer masterbatch is melted in an extruder, it is coaxially extruded on the outer surface of the conductor core, and after cooling, an insulating layer tightly wrapped on the conductor core is formed; then the aluminum-plastic tape is evenly and tightly wrapped around the insulating layer as a shielding layer coaxially arranged with the insulating layer, thereby obtaining an insulated shielded core; all the insulating shielded cores and the filling ropes used to fill the gaps are parallel to each other and then twisted together, and then the twisted insulating shielded cores and filling ropes are evenly and tightly wrapped with mica tape as a whole, thereby forming a flame retardant layer; after the outer sheath layer masterbatch is melted in an extruder, it is evenly extruded on the flame retardant layer, and after cooling, an outer sheath layer coaxially and tightly wrapped with the flame retardant layer is formed.
[0020] Among them, the filling rope is fluffy and elastic in its natural state. Therefore, during the concentrated twisting and mica tape wrapping process, the filling rope is further squeezed by the insulated shielding core or the mica tape, and the gap can be basically filled.
[0021] The beneficial effect of the present invention is that: the present scheme mainly improves the hydrophobicity of the sheath surface by adding fluororesin modification during the preparation process of the cable outer sheath layer, thereby more effectively inhibiting the accumulated water in the environment from penetrating through the outer sheath layer and entering the cable interior to affect the current transmission. And before adding the fluororesin, the fluororesin is first subjected to a certain degree of extrusion cross-linking treatment, so that when the fluororesin is subsequently blended and extruded with polyolefin to prepare the cable outer sheath layer, the fluororesin chain segment is less constrained by the matrix resin, the overall migration becomes stronger, the migration degree is improved, and finally more fluorine segments will be close to the sheath surface, which is conducive to further improving the waterproof and water-repellent performance of the sheath.
[0022] In addition, during the pre-treatment of fluororesins, it is necessary to focus on controlling the amount of extrusion cross-linking agent. Generally, the amount of cross-linking agent added is at least 1% or more of the resin weight, and the applicant controls this ratio at around 0.5%, mainly to avoid excessive restriction of the mobility of the chain segments after the fluororesin is cross-linked to a certain extent, which in turn leads to a decrease in the migration degree of the fluorine segments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a schematic cross-sectional view of the highly efficient waterproof layer structure cable of the present invention,
[0024] Among them, 1 is the conductor core, 2 is the insulation layer, 3 is the shielding layer, 4 is the flame retardant layer, 5 is the outer sheath layer, and 6 is the filling rope. DETAILED DESCRIPTION
[0025] The polyvinylidene fluoride involved in the following examples and comparative examples is PVDF JD-13 extrusion grade (Zhejiang Juhua), the polypropylene brand is S1003, the POE elastomer brand is 8150 (Dow, USA), and the other additives are also commercially available.
[0026] Example 1
[0027] (1) Preparation of fluororesin masterbatch
[0028] Calculated by weight, 100 parts of polyvinylidene fluoride, 0.5 parts of dicumyl peroxide, and 2 parts of zinc stearate were added to a high-speed mixer, stirred and mixed at a speed of 1200 r / min for 20 minutes, and then the mixture was added to a twin-screw extruder at 180-210° C. for blending, extrusion, and granulation;
[0029] (2) Preparation of outer sheath layer masterbatch
[0030] Calculated by weight, 100 parts of polypropylene, 15 parts of the fluororesin masterbatch obtained in step (1) of this embodiment, 16 parts of POE elastomer, 2 parts of zinc stearate, 0.4 parts of antioxidant 1010, and 9 parts of dioctyl phthalate are added to a high-speed mixer, stirred and mixed at a speed of 1500 r / min for 25 minutes, and then added to a twin-screw extruder at 160-200° C. for blending, extrusion, and granulation;
[0031] (3) Cable preparation
[0032] After the conventional insulating layer masterbatch is melted in an extruder, it is coaxially extruded on the outer surface of the conductor core, and after cooling, an insulating layer tightly wrapped on the conductor core is formed; then the aluminum-plastic tape is evenly and tightly wrapped around the insulating layer to form a shielding layer coaxially arranged with the insulating layer, thereby obtaining an insulated shielded wire core; seven such insulated shielded wire cores and several filling ropes used to fill the gaps between the insulated shielded wire cores are matched and concentrated together in parallel (the distribution of the insulated shielded wire cores: one on the inside, and six on the outside are evenly and tightly surrounded) and then twisted, Then, the insulated shielded wire core and the filling rope twisted together are wrapped evenly and tightly on the mica tape (double-sided mica tape with phlogopite paper as the base material and glass fiber cloth as the double-sided reinforcement material, the same below) as a whole, so as to form a flame retardant layer coaxially arranged with the whole; the outer sheath layer masterbatch obtained in step (2) of this embodiment is melt-extruded in an extruder at 170-200°C and evenly extruded on the flame retardant layer, and after cooling, an outer sheath layer coaxially and tightly covering the flame retardant layer is formed (after cooling and forming, the thickness of the outer sheath layer is about 1.8 mm, the same below).
[0033] Example 2
[0034] In the process of preparing the fluororesin masterbatch in step (1), the amount of the crosslinking agent added was reduced, and the remaining components and operations were the same as those in Example 1:
[0035] (1) Preparation of fluororesin masterbatch
[0036] Calculated by weight, 100 parts of polyvinylidene fluoride, 0.3 parts of dicumyl peroxide, and 2 parts of zinc stearate were added to a high-speed mixer, stirred and mixed at a speed of 1500 r / min for 20 minutes, and then the mixture was added to a twin-screw extruder at 180-210° C. for blending, extrusion, and granulation;
[0037] (2) Preparation of outer sheath layer masterbatch
[0038] Calculated by weight, 100 parts of polypropylene, 15 parts of the fluororesin masterbatch obtained in step (1) of this embodiment, 16 parts of POE elastomer, 2 parts of zinc stearate, 0.4 parts of antioxidant 1010, and 9 parts of dioctyl phthalate are added to a high-speed mixer, stirred and mixed at a speed of 1500 r / min for 25 minutes, and then added to a twin-screw extruder at 160-200° C. for blending, extrusion, and granulation;
[0039] (3) Cable preparation
[0040] After conventional insulating layer masterbatch is melted in an extruder, it is coaxially extruded on the outer surface of the conductor core, and after cooling, an insulating layer tightly wrapped on the conductor core is formed; then, an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer to form a shielding layer coaxially arranged with the insulating layer, thereby obtaining an insulating shielding core; seven such insulating shielding cores and a plurality of filling ropes used to fill the gaps between the insulating shielding cores are matched and concentrated together in parallel (the insulating shielding cores are distributed as follows: one on the inner side and six on the outer side are uniformly and tightly arranged in a circular shape), and then twisted together, and then the twisted insulating shielding cores and filling ropes are evenly and tightly wrapped with mica tape as a whole, thereby forming a flame retardant layer coaxially arranged with the whole; the outer sheath layer masterbatch obtained in step (2) of this embodiment is melted, extruded and evenly extruded on the flame retardant layer in an extruder at 170-200°C, and after cooling, an outer sheath layer coaxially tightly wrapped with the flame retardant layer is formed.
[0041] Example 3
[0042] In the process of preparing the fluororesin masterbatch in step (1), the amount of the crosslinking agent added is increased, and the remaining components and operations are the same as those in Example 1:
[0043] (1) Preparation of fluororesin masterbatch
[0044] Calculated by weight, 100 parts of polyvinylidene fluoride, 0.6 parts of dicumyl peroxide, and 2 parts of zinc stearate were added to a high-speed mixer, stirred and mixed at a speed of 1500r / min for 20 minutes, and then the mixture was added to a twin-screw extruder at 180-210°C for blending, extrusion, and granulation;
[0045] (2) Preparation of outer sheath layer masterbatch
[0046] Calculated by weight, 100 parts of polypropylene, 15 parts of the fluororesin masterbatch obtained in step (1) of this embodiment, 16 parts of POE elastomer, 2 parts of zinc stearate, 0.4 parts of antioxidant 1010, and 9 parts of dioctyl phthalate are added to a high-speed mixer, stirred and mixed at a speed of 1500 r / min for 25 minutes, and then added to a twin-screw extruder at 160-200° C. for blending, extrusion, and granulation;
[0047] (4) Cable preparation
[0048] After conventional insulating layer masterbatch is melted in an extruder, it is coaxially extruded on the outer surface of the conductor core, and after cooling, an insulating layer tightly wrapped on the conductor core is formed; then, an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer to form a shielding layer coaxially arranged with the insulating layer, thereby obtaining an insulating shielding core; seven such insulating shielding cores and a plurality of filling ropes used to fill the gaps between the insulating shielding cores are matched and concentrated together in parallel (the insulating shielding cores are distributed as follows: one on the inner side and six on the outer side are uniformly and tightly arranged in a circular shape), and then twisted together, and then the twisted insulating shielding cores and filling ropes are evenly and tightly wrapped with mica tape as a whole, thereby forming a flame retardant layer coaxially arranged with the whole; the outer sheath layer masterbatch obtained in step (2) of this embodiment is melted, extruded and evenly extruded on the flame retardant layer in an extruder at 170-200°C, and after cooling, an outer sheath layer coaxially tightly wrapped with the flame retardant layer is formed.
[0049] Example 4
[0050] (1) Preparation of fluororesin masterbatch
[0051] Calculated by weight, 100 parts of polyvinylidene fluoride, 0.4 parts of dicumyl peroxide, and 2 parts of zinc stearate were added to a high-speed mixer, stirred and mixed at a speed of 1200 r / min for 20 minutes, and then the mixture was added to a twin-screw extruder at 180-210° C. for blending, extrusion, and granulation;
[0052] (2) Preparation of outer sheath layer masterbatch
[0053] Calculated by weight, 100 parts of polypropylene, 20 parts of the fluororesin masterbatch obtained in step (1) of this embodiment, 10 parts of POE elastomer, 1.5 parts of zinc stearate, 0.5 parts of antioxidant 1010, and 6 parts of dioctyl phthalate are added to a high-speed mixer, stirred and mixed at a speed of 1500 r / min for 25 minutes, and then added to a twin-screw extruder at 160-200° C. for blending, extrusion, and granulation;
[0054] (3) Cable preparation
[0055] After conventional insulating layer masterbatch is melted in an extruder, it is coaxially extruded on the outer surface of the conductor core, and after cooling, an insulating layer tightly wrapped on the conductor core is formed; then, an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer to form a shielding layer coaxially arranged with the insulating layer, thereby obtaining an insulating shielding core; seven such insulating shielding cores and a plurality of filling ropes used to fill the gaps between the insulating shielding cores are matched and concentrated together in parallel (the insulating shielding cores are distributed as follows: one on the inner side and six on the outer side are uniformly and tightly arranged in a circular shape), and then twisted together, and then the twisted insulating shielding cores and filling ropes are evenly and tightly wrapped with mica tape as a whole, thereby forming a flame retardant layer coaxially arranged with the whole; the outer sheath layer masterbatch obtained in step (2) of this embodiment is melted, extruded and evenly extruded on the flame retardant layer in an extruder at 170-200°C, and after cooling, an outer sheath layer coaxially tightly wrapped with the flame retardant layer is formed.
[0056] Comparative Example 1
[0057] The outer sheath layer masterbatch is prepared by a conventional method, that is, the fluororesin is added to the matrix resin polypropylene without crosslinking, and the blending and extrusion granulation are carried out. The other components and operations are the same as those in Example 1:
[0058] (1) Preparation of outer sheath layer masterbatch:
[0059] Calculated by weight, 100 parts of polypropylene, 14.6 parts of polyvinylidene fluoride, 16 parts of POE elastomer, 2.3 parts of zinc stearate, 0.4 parts of antioxidant 1010, and 9 parts of dioctyl phthalate were added to a high-speed mixer, stirred and mixed at a speed of 1500r / min for 25 minutes, and then added to a twin-screw extruder at 160-200°C for blending, extrusion, and granulation;
[0060] (2) Cable preparation:
[0061] After conventional insulating layer masterbatch is melted in an extruder, it is coaxially extruded on the outer surface of the conductor core, and after cooling, an insulating layer tightly wrapped on the conductor core is formed; then, an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer to form a shielding layer coaxially arranged with the insulating layer, thereby obtaining an insulating shielding core; seven such insulating shielding cores and a plurality of filling ropes used to fill the gaps between the insulating shielding cores are matched and concentrated together in parallel (the insulating shielding cores are distributed as follows: one on the inner side and six on the outer side are uniformly and tightly arranged in a circular shape), and then twisted together, and then the twisted insulating shielding cores and filling ropes are evenly and tightly wrapped with mica tape as a whole, thereby forming a flame retardant layer coaxially arranged with the whole; the outer sheath layer masterbatch obtained in step (1) of this comparative example is melted, extruded and evenly extruded on the flame retardant layer in an extruder at 170-200°C, and after cooling, an outer sheath layer coaxially tightly wrapped with the flame retardant layer is formed.
[0062] Comparative Example 2
[0063] In the process of preparing the fluororesin masterbatch in step (1), the amount of the crosslinking agent added is further increased, and the remaining components and operations are the same as those in Example 1:
[0064] (1) Preparation of fluororesin masterbatch
[0065] Calculated by weight, 100 parts of polyvinylidene fluoride, 1 part of dicumyl peroxide, and 2 parts of zinc stearate were added to a high-speed mixer, stirred and mixed at a speed of 1500 r / min for 20 minutes, and then the mixture was added to a twin-screw extruder at 180-210° C. for blending, extrusion, and granulation;
[0066] (2) Preparation of outer sheath layer masterbatch
[0067] Calculated by weight, 100 parts of polypropylene, 15 parts of the fluororesin masterbatch obtained in step (1) of this comparative example, 16 parts of POE elastomer, 2 parts of zinc stearate, 0.4 parts of antioxidant 1010, and 9 parts of dioctyl phthalate are added to a high-speed mixer, stirred and mixed at a speed of 1500 r / min for 25 minutes, and then added to a twin-screw extruder at 160-200° C. for blending, extrusion, and granulation;
[0068] (3) Cable preparation
[0069] After conventional insulating layer masterbatch is melted in an extruder, it is coaxially extruded on the outer surface of the conductor core, and after cooling, an insulating layer tightly wrapped on the conductor core is formed; then, an aluminum-plastic tape is evenly and tightly wrapped around the insulating layer to form a shielding layer coaxially arranged with the insulating layer, thereby obtaining an insulating shielding core; seven such insulating shielding cores and a plurality of filling ropes used to fill the gaps between the insulating shielding cores are matched and concentrated together in parallel (the insulating shielding cores are distributed as follows: one on the inner side and six on the outer side are evenly and tightly arranged in a circular shape), and then twisted together, and then the twisted insulating shielding cores and filling ropes are evenly and tightly wrapped with mica tape as a whole, thereby forming a flame retardant layer coaxially arranged with the whole; the outer sheath layer masterbatch obtained in step (2) of this comparative example is melted, extruded and evenly extruded on the flame retardant layer in an extruder at 170-200°C, and after cooling, an outer sheath layer coaxially tightly wrapped with the flame retardant layer is formed.
[0070] The water absorption rate of the cables obtained in the above-mentioned embodiments and comparative embodiments was tested respectively: the prepared cable was cut to obtain a 15 cm long straight section as a sample (keeping the cut surface flush and parallel to the radial direction of the cable), and the sample was placed in a drying oven (50°C, relative humidity below 10%) for 24 hours to be fully dried, and then the sample was taken out and weighed, and the mass data was recorded as m1 (about 35 g); both ends of the sample in the length direction were wrapped and sealed with a flexible waterproof film and a rubber band (retaining a length of about 12 cm of the exposed part of the sample not wrapped by the flexible waterproof film), and then placed in a constant temperature and humidity test box (50°C, relative humidity 80%) for 72 hours to achieve water absorption treatment, and then the sample was taken out, and after removing the rubber bands and flexible waterproof films at both ends of the sample in the length direction, the observable moisture on the outer surface of the sample was absorbed and wiped off as soon as possible with a clean absorbent cloth (during this operation, it is necessary to avoid the moisture from transferring and contacting the exposed cross-sections at both ends of the sample in the length direction), and then weighed, and the mass data was recorded as m2. The water absorption rate of the cable sample is calculated based on the above measured data: water absorption rate = ((m2-m1) / m1) × 100%. The lower the water absorption rate, the better the waterproofness of the cable (sheath); the higher the water absorption rate, the worse the waterproofness of the cable (sheath). Three samples of the same product are measured and the average is taken. The details are shown in Table 1.
[0071] The outer sheath layers of the cables obtained in the above-mentioned embodiments and comparative embodiments were subjected to mechanical property tests according to the standard of GB / T 2951 "General Test Methods for Insulation and Sheath Materials of Electric and Optical Cables". Three samples of the same product were tested and the average was taken. The details are shown in Table 1.
[0072] Table 1
[0073]
[0074] In the above table, Examples 1 to 3 are significantly better than Comparative Example 1 in terms of waterproof effect.
[0075] Among them, Comparative Example 1 is a conventional extrusion modification process. The applicant believes that in this conventional blending extrusion modification process, polyvinylidene fluoride is mainly dispersed in the polypropylene matrix in the form of macromolecular long chains. During the migration to the surface of the extruded product, it will be more or less entangled by the surrounding polypropylene macromolecular chains, which ultimately leads to a part of the fluorine chain segments being unable to effectively migrate close to the surface of the extruded product.
[0076] In contrast, the applicant believes that, since the embodiments 1 to 3 of the present scheme have been subjected to appropriate extrusion cross-linking treatment on the polyvinylidene fluoride in advance, a number of polyvinylidene fluoride macromolecular chains can be relatively more stably combined and aggregated together. In the process of preparing the outer sheath layer by extrusion molding, the fluororesin in the masterbatch is dispersed in the polypropylene matrix under the strong shearing action of the extruder to form cross-linked units. At the same time, due to the poor compatibility between polyvinylidene fluoride itself and polypropylene, the matrix polypropylene macromolecular chain cannot really fully and effectively penetrate into these cross-linked units and effectively bind the cross-linked units. Ultimately, the binding effect of the matrix molecular chain on the cross-linked units of polyvinylidene fluoride in embodiments 1 to 3 of the present scheme is significantly less than the binding of the matrix molecular chain on each dispersed polyvinylidene fluoride molecular chain during the conventional extrusion modification of comparative example 1, so that the migration degree of the fluorine segment is more obvious in the extrusion molding process of embodiments 1 to 3 of the present scheme, and more fluorine segments can be enriched near the surface of the outer sheath layer of the cable after molding, which has a more ideal waterproof and water-resistant effect.
[0077] However, when the crosslinking of the fluororesin reaches a certain degree, as in Comparative Example 2, with the further increase in the amount of the crosslinking agent, the degree of crosslinking between the polyvinylidene fluoride molecular chains in each crosslinking unit formed increases accordingly, resulting in the corresponding shortening of the length of the fluorine segment between the crosslinking points in the crosslinking unit, resulting in a significant decrease in the segment movement activity, and the migration activity also decreases accordingly. Therefore, in Comparative Example 2, even if the binding constraint with the surrounding matrix polypropylene molecular chains is further reduced by increasing the degree of crosslinking, more fluororesins fail to effectively migrate to the surface of the product to exert a waterproof effect, but remain in the matrix, and the water-repellent effect is not improved.
[0078] The above speculation can also be confirmed to a certain extent from the changes in the mechanical properties of each embodiment and comparative example: compared with embodiment 1, the mechanical properties of embodiment 3 and comparative example 2 did not decline after the crosslinking degree increased, but slightly increased. This shows that the crosslinking degree of the fluororesin crosslinking unit in embodiment 1 is sufficient to inhibit the penetration of the matrix polypropylene molecular chain into it, and the crosslinking unit and the polypropylene molecular chain can no longer be effectively entangled and connected together. Otherwise, after the crosslinking degree increases, the overall mechanical properties should decline further (because further crosslinking will make the fluororesin crosslinking unit further get rid of the entanglement of the polypropylene molecular chain, so as to further distribute in the polypropylene matrix to form an island-like shape), but this is not the case with embodiment 3 and comparative example 2. The mechanical properties of embodiment 3 and comparative example 2 increase instead, because after the crosslinking degree increases further, the chain activity of the fluororesin crosslinking unit decreases, the migration degree becomes smaller, and thus it can be better dispersed in the matrix.
Claims
1. A highly efficient waterproof layer structure cable, characterized in that: The cable comprises one or more insulating shielded wire cores, each of the insulating shielded wire cores comprises a conductor wire core (1), an insulating layer (2) tightly wrapped outside the conductor wire core (1), and a shielding layer (3) tightly wrapped outside the insulating layer (2); all the insulating shielded wire cores are twisted together as a whole and are tightly wrapped by a flame retardant layer (4); the cable also comprises an outer sheath layer (5) tightly wrapped outside the flame retardant layer (4), The outer sheath layer (5) comprises, by weight, 100 parts of polyolefin, 10-20 parts of fluororesin masterbatch, 10-20 parts of POE elastomer, 1-2.5 parts of first lubricant, 0.1-0.5 parts of antioxidant, and 3-10 parts of plasticizer. The fluororesin masterbatch comprises, by weight, 100 parts of polyvinylidene fluoride, 0.3 to 0.6 parts of a cross-linking agent, and 1 to 2 parts of a second lubricant.
2. The highly efficient waterproof layer structure cable as claimed in claim 1, characterized in that: There are more than two insulating shielding wire cores, and the inner side of the flame retardant layer (4) and the gaps between the insulating shielding wire cores are filled with filling ropes (6).
3. The highly efficient waterproof layer structure cable according to claim 1, characterized in that: The fluororesin masterbatch is prepared by adding the polyvinylidene fluoride, the crosslinking agent and the second lubricant into a high-speed mixer, stirring and mixing them sufficiently, and then adding them into an extruder for blending, extrusion and granulation.
4. The highly efficient waterproof layer structure cable as claimed in claim 1, characterized in that: The preparation method of the outer sheath layer (5) is as follows: adding the polyolefin, the fluororesin masterbatch, the POE elastomer, the first lubricant, the antioxidant, and the plasticizer into a high-speed mixer, stirring and mixing them thoroughly, and then adding them into an extruder for blending, extrusion, and granulation to obtain the outer sheath layer masterbatch; then, melting the outer sheath layer masterbatch in the extruder, uniformly extruding it onto the surface of the flame retardant layer (4), and cooling it to form the outer sheath layer (5).
5. The highly efficient waterproof layer structure cable according to claim 1, characterized in that: The polyolefin is polyethylene or polypropylene.
6. The highly efficient waterproof layer structure cable according to claim 1, characterized in that: The crosslinking agent is a peroxide crosslinking agent.
7. The highly efficient waterproof layer structure cable according to claim 1, characterized in that: The antioxidant is a phenolic antioxidant.
8. The highly efficient waterproof layer structure cable according to claim 1, characterized in that: The manufacturing method of the cable comprises the following steps: melting the insulating layer masterbatch in an extruder, coaxially extruding it on the outer surface of the conductor core (1), and cooling it to form the insulating layer (2) tightly covering the conductor core (1); then evenly and tightly wrapping an aluminum-plastic tape around the insulating layer (2) to form the shielding layer (3) coaxially arranged with the insulating layer (2), thereby obtaining the insulating shielding core; twisting all the insulating shielding cores together, and evenly and tightly wrapping them with mica tape to form the flame retardant layer (4); melting the outer sheath layer masterbatch in an extruder, and evenly extruding it on the surface of the flame retardant layer (4), and cooling it to form the outer sheath layer (5).
9. The highly efficient waterproof layer structure cable as claimed in claim 2, characterized in that: The manufacturing method of the cable comprises the following steps: melting the insulating layer masterbatch in an extruder, coaxially extruding it on the outer surface of the conductor core (1), and cooling it to form the insulating layer (2) tightly covering the conductor core (1); then evenly and tightly wrapping an aluminum-plastic tape around the insulating layer (2) to form the shielding layer (3) coaxially arranged with the insulating layer (2), thereby obtaining the insulating shielding core; combining all the insulating shielding cores and the filling rope (6) for filling the gaps in parallel with each other and then twisting them together, and then evenly and tightly wrapping the twisted insulating shielding cores and the filling rope (6) as a whole with mica tape, thereby forming the flame retardant layer (4); melting the outer sheath layer masterbatch in an extruder, evenly extruding it on the surface of the flame retardant layer (4), and cooling it to form the outer sheath layer (5).